Global logistics of an iron-based energy network: A case study of retrofitting german coal power plants - Erik Jansen; Julia Schuler; Armin Ardone; Viktor Slednev; Wolf Fichtner; Marc E. Pfetsch (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2023)
For the global transition of energy systems, the establishment of new energy storage and carrier media to balance the geographical and temporal availability of renewable energy is a necessity. In this context, the interdisciplinary cluster project Clean Circles is investigating the potential of an iron-based circular energy economy. Compared to hydrogen, an energy carrier produced from renewables through electrolysis and widely discussed option for future global energy trade, iron offers several advantages. An ironbased circular energy economy re-uses existing infrastructure associated with the transportation of and the electricity generation from coal. In this paper, we present a model-based approach for the cost-minimal selection of energy export regions and logistic routes to import iron for electricity generation to power plant sites in Germany and return iron oxide to reduction plants in the export regions. To demonstrate the performance of the model, we conduct a case study of operating all German hard coalfired power plants in operation in 2030 on iron. For the iron reduction process site selection, we provide the optimization with renewable energy potentials and costs in coastal regions of MENA and Patagonia.
Keywords: 330; Kreislaufwirtschaft; Erneuerbare Energie; Deutschland